2019
DOI: 10.1021/acs.jpcc.8b11431
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Elucidation of Electrochemical CO2 Reduction on an Electrodeposited Cu3Sn Alloy

Abstract: The reaction selectivity of an electrode catalyst can be modulated by regulating its crystal structure, and the modified electrode may show different CO2 reduction selectivity from that of its constituent metal. In this study, we investigated the mechanisms of the electrochemical CO2 reduction on an electrodeposited Cu3Sn alloy by experimental and theoretical analyses. The electrodeposited Cu3Sn alloy electrode showed selectivity for CO production at all the applied potentials, and HCOOH production increased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
5
21
1
Order By: Relevance
“…S15 online). In contrast to CO 2 RR performance of the Snbased catalysts reported so far [5,6,19,[30][31][32][35][36][37][38], the Sn-Cu alloy in this work exhibits an excellent activity, indicating the Sn-Cu alloy is promising for the prospective applications of CO 2 RR. In-situ XANES spectra results suggest that the Sn element keeps its positive charge state under the CO 2 RR condition (Fig.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…S15 online). In contrast to CO 2 RR performance of the Snbased catalysts reported so far [5,6,19,[30][31][32][35][36][37][38], the Sn-Cu alloy in this work exhibits an excellent activity, indicating the Sn-Cu alloy is promising for the prospective applications of CO 2 RR. In-situ XANES spectra results suggest that the Sn element keeps its positive charge state under the CO 2 RR condition (Fig.…”
Section: Resultscontrasting
confidence: 69%
“…Although these catalysts own appreciable Faradaic efficiencies towards formate at high overpotentials, they still suffer from poor mass activity. Alloying Sn or Cu with the other element is a potential avenue to promote the CO 2 RR performance, which is attained by modulating the binding energies of reaction intermediates through tailoring surface electronic structure of the alloys [33][34][35]. For instance, Pd-Sn alloy catalysts inhibited the competitive hydrogen evolution reaction (HER), whereas selectively improved the CO 2 RR performance [36].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that the j HCOO − of Cu 3 Sn@Cu‐SnO 2 NWs (∼30 mA cm −2 ) is much higher than that of Cu 3 Sn/CF (∼10 mA cm −2 ) at −0.9 V (Figure 3d), further testifying the enhanced catalytic activity and selectivity of Cu 3 Sn@Cu‐SnO 2 NW toward the CO 2 RR. Moreover, the catalytic performance of Cu 3 Sn@Cu‐SnO 2 is superior or comparable to that of previously reported catalysts, including Cu 3 Sn alloy (FE HCOO − =50 %, j HCOO − =1.4 mA cm −2 ), [27] Cu 6 Sn 5 NPs/CB (FE HCOO − =65.3 %, j HCOO − =7.5 mA cm −2 ), [28] CuSn NPs/C−A (FE HCOO − =71.5 %, j HCOO − =12.6 mA cm −2 ) [29] and so forth (Figure 4e and Table S1). The good catalytic activity should derive from the typical core‐shell nanowire structure and Cu doped SnO 2 amorphous layer, which is beneficial to both depress the HER process and promote the conversion from CO 2 to formate.…”
Section: Resultssupporting
confidence: 70%
“…[20] Recent studies also confirmed the favored CO-pathway on the Cu-Sn alloys with lower Sn amount (e.g., Cu 3 Sn). [21,22] On the other hand, the concept of entropy has already been introduced for analyses of binary alloys. [23] For example, Takeguchi et al proposed an entropy-based adsorption theory that alloys with random distributions (defined by coordination state in their work with PtRu alloys) can weaken the adsorption of *CO. [24] Thus, highentropy state CuSn alloys like Cu 6 Sn 5 are possibly not suitable for *CO adsorption, [21] while a low-entropy state CuSn alloy may provide an enhanced capability for *CO adsorption and subsequent enhanced ethanol selectivity.In this work, we developed a low-entropy Cu 3 Sn electrocatalyst with substantially enhanced adsorption of *CO and *CHCHOH as key intermediates for ethanol production, featuring as efficient electrochemical CO 2 reduction to ethanol.Electrochemical carbon dioxide reduction to ethanol suggests a potential strategy to reduce the CO 2 level and generate valuable liquid fuels, while the development of low-cost catalysts with high activity and selectivity remains a major challenge.…”
mentioning
confidence: 99%